Novel UV led photopolymerization and characterization for polyacrylamide and poly (n-isopropylacrylamide) hydrogels - Nur Farizah Ayub, 1989-, author 602198; Mohd. Hafiz Dzarfan Othman, supervisor 603545; Nadia Adrus, supervisor 326021; Shahrir Hashim, supervisor 179229; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga 599090 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Polimer))